Evaluasi Proses Bisnis Dompet Digital Menggunakan Technology Acceptance Model - Alika Zuhaira, Ismi; Alijoyo, Fransiscus Antonius (Institut Teknologi Garut, 2024)
The aim of the research is to evaluate the digital wallet business process by measuring the satisfaction of Dana application users. The model that will be used to measure satisfaction is the Technology Acceptance Model (TAM) method. Data from 139 DANA user respondents via online questionnaire using convenience sampling technique with an error margin of 9%. Based on calculations using the SmartPLS 4.0 application, all variables in the TAM model influence each other, namely perceived usefulness, perceived ease of use, perceived credibility, attitude toward using, behavioral intention to use, acceptance of IT, and actual system use. Except that the perceived ease of use variable has no significant effect on attitude toward using. This research provides insight for digital wallet providers to increase user satisfaction by focusing on aspects of completeness of features and information, transfer processes between accounts, and ease of using the application. Practical implications include marketing strategy and application development. Future research could involve larger samples and additional factors that influence digital wallet application user satisfaction.